Aplikasi Point Of Sales Berbasis Client Server Dengan Php Dan Mysql Pada Toko Ibu Sum - Suherman Suherman (Teknik Informatika, Universitas Pelita Bangsa, 2018)
In this increasingly modern age, the development of science and technology is increasingly rapid, especially now that information is very rapidly spreading throughout the world. In line with this, the problems that exist in the company are also increasingly complex in everyday life. With this reality we are required to solve existing problems by utilizing technological sophistication and speed, accuracy and accuracy in providing information so that in carrying out our work we get optimal results. One of them is the use of computer technology. Sales is one of the important business activities carried out by companies to be able to obtain profits which are the main objectives of most companies. To be able to carry out sales activities well, every business owner needs to have a good and controlled system with a clear path. So based on the description above, it is very interesting to conduct a study of mom sum shop to support and improve performance and efficiency in selling their products